Efficacy of respiratory cytology in the diagnosis of lung lesion - Junmuenwai, Wanwisa (Maharat Nakhon Ratchasima Hospital Journal, 2024)
All 324 cases were investigated for the lung lesion between January 2015 and December 2016 in Department of Anatomical Pathology of Maharat Nakorn Ratchasima Hospital, under the fiberoptic flexible bronchoscopy for collecting the samples of bronchoalveolar lavage and bronchial washing for cytology as well as simultaneous bronchial biopsy for histology. All samples were taken and processed under standard procedures of cytology and histology. The aim of this study was to evaluate diagnostic efficacy of Bronchial wash and Bronchoalveolar lavage cytology, compared with the bronchial biopsy as the gold standard diagnostic test. There were 204 samples of Bronchial wash cytology (63%) and 120 of Bronchoalveolar lavage (37%). The bronchial wash cytology showed the sensitivity 39.4%, specificity 98.1% and accuracy 69.6%. The Bronchoalveolar lavage cytology showed the sensitivity 36.2%, specificity 95.9% and accuracy 72.5%. In the patients with malignant histopathology, the most common age group was between 61 and 70 years of age, male to female ratio was 1.8: 1 and the right lung was predominantly found (56.9%). The common presenting symptoms were cough (66.4%) and dyspnea (39.8%). The most common type of tumor was adenocarcinoma (62.1%). Smoking was found in 64.3 % of malignancy group. It was concluded that bronchial wash cytology and Bronchoalveolar lavage cytology were a safe, rapid and cost-effective tool for the diagnosis.